Long‐term application of mineral fertilizer weakens the stability of microbial N‐transforming functions via the decrease of soil microbial diversity - Zhou Zhang; Ruirui Chen; Evgenia Blagodatskaya; Sergey Blagodatsky; Deyan Liu; Yongjie Yu; Xiaolin Zhu; Youzhi Feng (Journal of Sustainable Agriculture and Environment)
Abstract Introduction Ensuring functional stability is crucial for the sustainable development and soil health of agroecosystems amidst escalating climate changes. Although mineral fertilization is known to enhance the strength of soil N‐transforming functions, its effects on functional stability remain unclear. Materials & Methods This study evaluated three stability components (resistance, resilience, and recovery), along with the dimensionality of soil microbial N‐transforming functions during drought‐rewetting process. We investigated enzymatic activity and functional gene abundances after 10 years of fertilization under three strategies, mineral fertilization (NPK), mineral fertilization plus organic amendments (OMN), and no fertilization (CK). Results The resistance was 0.60, 0.66 and 0.56; the resilience was 0.46, 0.28 and 0.46; and the recovery was 0.83, 0.73 and 0.82, respectively in the CK, NPK and OMN treatments. Soils with long‐term mineral fertilization exhibited the highest resistance but the lowest resilience and recovery during drought‐rewetting. Furthermore, mineral fertilization demonstrated the lowest dimensionality of stability, with smallest ellipsoid volume and most negative correlations. Soil microbial alpha diversity was identified as a key predictor of functional stability, positively correlating with stability across fertilization strategies. Conclusion Mineral fertilization, which decreased alpha diversity, posed challenges for sustainable development of agroecosystems under drought conditions. Mineral fertilization plus organic amendments provided strong N‐transforming functions and moderate stability, making it as an optimal fertilization strategy. These results offer valuable insights for optimizing agroecosystem management and advancing soil sustainability.